2018
DOI: 10.1186/s40780-018-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fall-related adverse events among older adults using the Japanese Adverse Drug Event Report (JADER) database

Abstract: BackgroundFalls are a common but serious problem in older adults, and may lead to fractures and bleeding. As many factors, such as medication, aging, and comorbid diseases may simultaneously affect fall-related adverse events (AEs) in older adults, we evaluated the association between fall-related AEs and the use of medication, aging, and comorbid diseases using the Japanese Adverse Drug Event Report (JADER) database.MethodsWe analyzed reports of fall-related AEs associated with α-blockers, diuretics, calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Retrospective data analysis was performed using two different RWD in Japan. The Japanese Adverse Drug Event Report (JADER), a public spontaneous ADR database constructed by the Pharmaceuticals and Medical Devices Agency (PMDA), and a large prescription database constructed by a database vendor (Japan Medical Information Research Institute, Inc Japan [JMIRI]) database were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Retrospective data analysis was performed using two different RWD in Japan. The Japanese Adverse Drug Event Report (JADER), a public spontaneous ADR database constructed by the Pharmaceuticals and Medical Devices Agency (PMDA), and a large prescription database constructed by a database vendor (Japan Medical Information Research Institute, Inc Japan [JMIRI]) database were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Based on an SRS database, data mining algorithms have been developed to identify drug-associated adverse events (AEs) as signals using reporting odds ratio (ROR) by employing a stepwise method. We previously reported that the concomitant use of drugs might increase the risk of AEs using these approaches [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The reporting odds ratio (ROR) has been used to derive an index for detecting drug-associated adverse events (AEs) [7,8]. We previously analyzed an SRS database and found that the combination of medications might increase the risk of AEs according to the index derived from the RORs [10][11][12]. In this study, we evaluated the anti-infectives-related AKI pro les using ROR.…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating the adjusted RORs using a multivariate logistic regression analysis technique, Abe et al showed that polypharmacy and age might be more closely linked to an increased risk of kidney disorder than liver disorder [10]. Association rule mining in large databases is a new analytical approach for evaluating association rules between variables [11,17]. Hatahira et al applied this algorithm to assess the association rules among fall-related AEs, the number of administered drugs, and age in the JADER database [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation